Routes to high-performance layered oxide cathodes for sodium-ion batteries - Wang, Jingqiang; Zhu, Yan-Fang; Su, Yu; Guo, Jun-Xu; Chen, Shuangqiang; Liu, Hua-Kun; Dou, Shi-Xue; Chou, Shu-Lei; Xiao, Yao (Chemical Society reviews, 2024)
Sodium-ion batteries (SIBs) are experiencing a large-scale renaissance to supplement or replace expensive lithium-ion batteries (LIBs) and low energy density lead-acid batteries in electrical energy storage systems and other applications. In this case, layered oxide materials have become one of the most popular cathode candidates for SIBs because of their low cost and comparatively facile synthesis method. However, the intrinsic shortcomings of layered oxide cathodes, which severely limit their commercialization process, urgently need to be addressed. In this review, inherent challenges associated with layered oxide cathodes for SIBs, such as their irreversible multiphase transition, poor air stability, and low energy density, are systematically summarized and discussed, together with strategies to overcome these dilemmas through bulk phase modulation, surface/interface modification, functional structure manipulation, and cationic and anionic redox optimization. Emphasis is placed on investigating variations in the chemical composition and structural configuration of layered oxide cathodes and how they affect the electrochemical behavior of the cathodes to illustrate how these issues can be addressed. The summary of failure mechanisms and corresponding modification strategies of layered oxide cathodes presented herein provides a valuable reference for scientific and practical issues related to the development of SIBs.